The associations between staffing hours and quality of care indicators in long-term care - Veronique M Boscart; Souraya Sidani; Jeffrey Poss; Meaghan Davey; Josie d'Avernas; Paul Brown; George Heckman; Jenny Ploeg; Andrew P Costa (BMC, 2018)
Abstract Background Long-term care (LTC) staffing practices are poorly understood as is their influence on quality of care. We examined the relationship between staffing characteristics and residents' quality of care indicators at the unit level in LTC homes. Methods This cross-sectional study collected data from administrative records and resident assessments from July 2014 to June 2015 at 11 LTC homes in Ontario, Canada comprising of 55 units and 32 residents in each unit. The sample included 69 registered nurses, 183 licensed/registered practical nurses, 858 nursing assistants, and 2173 residents. Practice sensitive, risk-adjusted quality indicators were described individually, then combined to create a quality of care composite ranking per unit. A multilevel regression model was used to estimate the association between staffing characteristics and quality of care composite ranking scores. Results Nursing assistants provided the majority of direct care hours in LTC homes (76.5%). The delivery of nursing assistant care hours per resident per day was significantly associated with higher quality of resident care (p = < 0.01). There were small but significant associations with quality of care for nursing assistants with seven or more years of experience (p = 0.02), nursing assistants late to shift (p = < 0.01) and licensed/registered practical nurses late to shift (p = 0.02). Conclusions The number of care hours per resident per day delivered by NAs is an important contributor to residents' quality of care in LTC homes. These findings can inform hiring and retention strategies for NAs in LTC, as well as examine opportunities to optimize the NA role in these settings.